Tailoring the radiation tolerance of vanadate–phosphate fluorapatites by chemical composition control - Lu, Fengyuan (2013)
The apatite-type structure of AI4AII6(BO4)6(OH, F, Cl)2 (AI, AII = Ca, Na, rare earths, fission product elements such as I and Tc, and/or actinides; B = Si, P, V, or Cr) offers unique structural advantages as an advanced nuclear waste form because a wide variety of actinides and fission products can be incorporated into the structure through coupled cation and anion substitutions. However, apatite undergoes a radiation-induced crystalline-to-amorphous transition, and previously, the effect of composition on the radiation-induced transformation has not been well understood. In this study, we demonstrate that vanadate–phosphate fluorapatite's radiation tolerance can be controlled by varying the composition. Enhanced radiation tolerance is achieved by replacing vanadium with phosphorus at the B-site or by replacing Pb with Ca at the A-site. Correlations among chemical composition, radiation performance and electronic to nuclear stopping power ratio were demonstrated and suggest that the ionization process resulting from electronic energy loss may enhance annealing of defects upon radiation damage.